Preparation method of low VOC high performance ship anticorrosive and antifouling integrated coating

CN122941272APending Publication Date: 2026-10-20GECKO (ZHEJIANG) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611297441.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]然而,海洋环境的高温、高湿、高盐特性对涂层耐久性构成严峻挑战

Benefits of technology

本发明以水性环氧乳液为成膜物质,与脂肪族胺水性分散体复配,不仅大幅降低VOC含量,避免传统溶剂型涂料对环境和人体的危害,而且通过与防锈颜料复配,所形成的致密纯化膜既不溶于水,硬度又高,附着力优异,结合负载二氧化硅作用,形成致密物理屏障,有效阻隔腐蚀介质渗透。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1787652632368-000001
    Figure REF-OBJ-1787652632368-000001
  • Figure NLAXJKIXFRKXLRCMXVRB7BSQMPGZCFRPVVYLB4XY
    Figure NLAXJKIXFRKXLRCMXVRB7BSQMPGZCFRPVVYLB4XY
  • Figure PGL9RRXGC2IQIL6XDSD6LX2WAR34ZZR9E6ULUZNC
    Figure PGL9RRXGC2IQIL6XDSD6LX2WAR34ZZR9E6ULUZNC
Patent Text Reader

Abstract

This invention relates to the field of anti-corrosion and antifouling coating technology, and more particularly to a method for preparing a low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships. The raw materials of the aforementioned low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships, by weight, include: 30-40 parts of waterborne epoxy emulsion, 1-5 parts of supported silica, 1-5 parts of graphene oxide, 5-15 parts of filler, 10-20 parts of anti-rust pigment, 1-3 parts of dispersant, 5-15 parts of aliphatic amine waterborne dispersion, and 1-5 parts of propylene glycol methyl ether. The coating obtained by this invention can maintain structural integrity in high-temperature, high-humidity, and high-salt marine environments, significantly extending the service life of ships, offshore platforms, and other facilities, and reducing maintenance costs and the risk of safety accidents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anti-corrosion and antifouling coating technology, and in particular to a method for preparing a low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships. Background Technology

[0002] With the continuous expansion of infrastructure construction and rapid development of the national economy, anti-corrosion coating of steel facilities has become a core issue in the field of anti-corrosion engineering. Especially in scenarios such as ships and offshore platforms that are exposed to harsh marine environments for extended periods, high-performance anti-corrosion coatings are a key barrier to ensure the safe operation of these facilities.

[0003] Currently, solvent-based coatings are still the main method for steel structure corrosion protection. Among them, solvent-based epoxy resins are widely used due to their excellent performance, but their high emissions of volatile organic compounds (VOCs) seriously pollute the environment and endanger human health. With increasingly stringent environmental regulations, the industry is shifting from traditional high-VOC solvent-based formulations to low-VOC formulations. Waterborne epoxy resin coatings, which combine environmental friendliness and protective performance, have become an important development direction.

[0004] However, the high temperature, high humidity, and high salinity of the marine environment pose a severe challenge to the durability of coatings. Corrosive media can easily penetrate the pores of the coating, compromising its physical shielding function and leading to a decrease in protective effectiveness. Simultaneously, the attachment of marine microorganisms (such as bacteria and microalgae) to the coating surface triggers a chain reaction: on the one hand, the microbial community forms a biofilm, promoting the colonization of large fouling organisms, significantly increasing facility weight, reducing fluid efficiency, and exacerbating energy consumption; on the other hand, localized peeling of the biofilm can induce galvanic corrosion, accelerating the failure of the metal substrate and greatly shortening the service life of the coating.

[0005] Therefore, developing a marine coating that combines low VOC emissions, long-lasting corrosion protection, and resistance to biofouling is of great practical significance for improving the durability of marine facilities, ensuring navigation safety, and reducing operation and maintenance costs, and has excellent research prospects. Summary of the Invention

[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing a low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships.

[0007] A low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships comprises the following raw materials by weight: 30-40 parts of waterborne epoxy emulsion, 1-5 parts of loaded silica, 1-5 parts of graphene oxide, 5-15 parts of filler, 10-20 parts of anti-rust pigment, 1-3 parts of dispersant, 5-15 parts of aliphatic amine waterborne dispersion, and 1-5 parts of propylene glycol methyl ether.

[0008] Preferably, the aqueous epoxy emulsion is a liquid epoxy resin dispersion.

[0009] Preferably, the anti-rust pigment is at least one of zinc phosphate, titanium phosphate, zinc benzoate, and aluminum tripolyphosphate; the filler is at least one of precipitated barium sulfate, wollastonite powder, kaolin, and mica powder.

[0010] Preferably, the dispersant is a sodium hexametaphosphate dispersant.

[0011] Preferably, the loaded silica is prepared by the following steps: hexadecyltrimethylammonium chloride is added to an aqueous ethanol solution and stirred until homogeneous. Triethanolamine is added, and the pH of the system is adjusted to 9-10. Under nitrogen protection, tetraethyl orthosilicate and mercaptopropyltriethoxysilane are added while stirring. The mixture is refluxed at 60-70°C for 1-2 hours. Amino-terminated polyamide amine and zinc acetate are added, and stirring is continued for 1-4 hours. The mixture is then centrifuged, washed, and vacuum dried.

[0012] Preferably, the mass ratio of hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl orthosilicate, mercaptopropyltriethoxysilane, amino-terminated polyamide amine, and zinc acetate is 1-2:1-3:5-10:1-2:1-5:1-2.

[0013] Preferably, the mass fraction of the ethanol aqueous solution is 20-50%.

[0014] The preparation method of the above-mentioned low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships includes the following steps: S1. Continuously stir the water, and add filler, anti-rust pigment, graphene oxide and dispersant in sequence during the stirring process. Continue stirring for 10-15 minutes, add water-based epoxy emulsion and loaded silica and stir evenly. Filter to obtain component A. S2. Mix the aliphatic amine aqueous dispersion, propylene glycol methyl ether, and water for 15-20 minutes to obtain component B.

[0015] Preferably, in S1, a 90-110 mesh filter is used for filtration.

[0016] The above-mentioned low-VOC high-performance integrated anti-corrosion and anti-fouling coating for ships is applied by continuously stirring component A, adding component B during the stirring process, continuing to stir for 10-20 minutes after the addition is complete, and then filtering.

[0017] Compared with existing technologies, the present invention has the following advantages: This invention uses waterborne epoxy emulsion as the film-forming substance and combines it with aliphatic amine waterborne dispersion. This not only significantly reduces VOC content and avoids the harm to the environment and human body caused by traditional solvent-based coatings, but also, through combination with anti-rust pigments, forms a dense and purified film that is insoluble in water, has high hardness, and excellent adhesion. Combined with the effect of loaded silica, it forms a dense physical barrier that effectively blocks the penetration of corrosive media.

[0018] The obtained loaded silica in the application utilizes hydrolysis and condensation of ethyl silicate to form a silica skeleton, and a mercapto group is introduced by cooperation of mercaptopropyl triethoxysilane, and the end amino polyamide is cooperated with zinc acetate, and is fixed by coordination and amino action of mercapto-Zn 2+ The product not only can effectively inhibit the initial adhesion of microorganisms such as bacteria and microalgae on the surface of the coating, reduce the adhesion of large-scale fouling organisms, but also has synergistic effect with the water-based epoxy emulsion after curing, the adhesion is significantly enhanced, and has excellent impact resistance.

[0019] The obtained coating in the application can maintain structural integrity in the high-temperature, high-humidity and high-salt environment of the sea, significantly prolong the service life of facilities such as ships and offshore platforms, and reduce maintenance costs and safety accident risks. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The impact resistance and adhesion of the coating made of the coating obtained from Example 5 and Comparative Examples 1-2 are compared.

[0021] Figure 2 The fouling coverage area percentage of the coating made of the coating obtained from Example 5 and Comparative Examples 1-2 is plotted against time. DETAILED DESCRIPTION

[0022] The application will be further described in detail below in combination with specific embodiments, and the examples given are only for illustrating the application, not for limiting the scope of the application. The examples provided below can be used as a guide for further improvement by those skilled in the art, and do not constitute any limitation on the application.

[0023] In the following examples, the experimental methods are conventional methods, and are carried out according to the techniques or conditions described in the literature in the art or according to the product instructions, unless otherwise specified. The materials, reagents, etc. used in the following examples can be obtained commercially, unless otherwise specified.

[0024] The liquid epoxy resin dispersion used in the following is purchased from Shenzhen Huanya New Material Technology Co., Ltd., and the model number is HY-5621. The graphene oxide used in the following is purchased from Jiangxi Suobang New Material Technology Co., Ltd., and the particle size is <4 μm. The aliphatic amine aqueous dispersion (593 curing agent) used in the following is purchased from Jining Fanghe Chemical Co., Ltd. The end amino polyamide amine (PAMAM, G3.0) used in the following is purchased from Hangzhou Xinqiao Biological Technology Co., Ltd.

[0025] Example 1

[0026] A low VOC high performance ship anticorrosion and antifouling integrated coating, the raw materials of which comprise: liquid epoxy resin dispersion 30g, loaded silica 1g, graphene oxide 1g, precipitated barium sulfate 5g, zinc phosphate 10g, sodium hexametaphosphate 1g, aliphatic amine aqueous dispersion 5g, propylene glycol methyl ether 1g.

[0027] The loaded silica is prepared by the following steps: 1g of cetyltrimethylammonium chloride is added to 50g of 20% mass fraction ethanol aqueous solution and stirred uniformly, 1g of triethanolamine is added, the pH value of the system is adjusted to 9-10, 5g of tetraethyl orthosilicate and 1g of mercaptopropyl triethoxysilane are added under nitrogen protection and stirring, reflux stirring is carried out at 60℃ for 1h, 1g of amino-terminated polyamide amine and 1g of zinc acetate are added and continue to stir for 1h, centrifugation, washing and vacuum drying are carried out.

[0028] The preparation method of the above-mentioned low VOC high performance ship anticorrosion and antifouling integrated coating comprises the following steps: S1, 20g of water is continuously stirred, and precipitated barium sulfate, zinc phosphate, graphene oxide and sodium hexametaphosphate are sequentially added during stirring, continue to stir for 10min at a stirring speed of 1000r / min, add liquid epoxy resin dispersion and loaded silica and stir uniformly, filter with a 90 mesh filter screen to obtain component A; S2, aliphatic amine aqueous dispersion, propylene glycol methyl ether and 5g of water are mixed for 15min at a stirring speed of 400r / min to obtain component B.

[0029] The use method of the above-mentioned low VOC high performance ship anticorrosion and antifouling integrated coating, component A is continuously stirred, component B is added during stirring, and continue to stir for 10min after addition is completed, and filter with a 40 mesh filter screen.

[0030] Example 2

[0031] A low VOC high performance ship anticorrosion and antifouling integrated coating, the raw materials of which comprise: liquid epoxy resin dispersion 40g, loaded silica 5g, graphene oxide 5g, precipitated barium sulfate 15g, aluminum tripolyphosphate 20g, sodium hexametaphosphate 3g, aliphatic amine aqueous dispersion 15g, propylene glycol methyl ether 5g.

[0032] The loaded silica is prepared by the following steps: 2g of cetyltrimethylammonium chloride is added to 60g of 50% mass fraction ethanol aqueous solution and stirred uniformly, 3g of triethanolamine is added, the pH value of the system is adjusted to 8-10, 10g of tetraethyl orthosilicate and 2g of mercaptopropyl triethoxysilane are added under nitrogen protection and stirring at a temperature of 70℃, reflux stirring is carried out for 2h, 5g of amino-terminated polyamide amine and 2g of zinc acetate are added and continue to stir for 4h, centrifugation, washing and vacuum drying are carried out.

[0033] The preparation method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises the following steps: S1, continuously stir 40g of water, and sequentially add precipitated barium sulfate, aluminum tripolyphosphate, graphene oxide, and sodium hexametaphosphate during the stirring process; continue stirring for 15min at a stirring speed of 1500r / min; uniformly stir the liquid epoxy resin dispersion and the loaded silicon dioxide; filter using a 110-mesh filter screen to obtain component A; S2, mix the aliphatic amine aqueous dispersion, propylene glycol methyl ether, and 10g of water for 20min at a stirring speed of 600r / min to obtain component B.

[0034] The use method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises continuously stirring component A, adding component B during the stirring process, and continuing to stir for 20min after the addition is completed; and filtering using an 80-mesh filter screen.

[0035] Example 3

[0036] A low-VOC high-performance ship anticorrosive and antifouling integrated coating, raw materials of which comprise: 33g of liquid epoxy resin dispersion, 4g of loaded silicon dioxide, 2g of graphene oxide, 12g of kaolin, 12g of titanium phosphate, 2.5g of sodium hexametaphosphate, 8g of aliphatic amine aqueous dispersion, and 4g of propylene glycol methyl ether.

[0037] The loaded silicon dioxide is prepared by the following steps: 1.2g of cetyltrimethylammonium chloride is added to 58g of a 30% mass fraction ethanol aqueous solution and stirred uniformly; 2.5g of triethanolamine is added, and the pH value of the system is adjusted to 9-10; 7g of tetraethyl orthosilicate and 1.8g of mercaptopropyl triethoxysilane are added thereto under nitrogen protection in a stirring state; reflux stirring is performed at a temperature of 62℃ for 100min; 2g of amino-terminated polyamide amine and 1.8g of zinc acetate are added and continue to stir for 2h; centrifugation, washing, and vacuum drying are performed.

[0038] The preparation method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises the following steps: S1, continuously stir 40g of water, and sequentially add precipitated barium sulfate, aluminum tripolyphosphate, graphene oxide, and sodium hexametaphosphate during the stirring process; continue stirring for 15min at a stirring speed of 1500r / min; uniformly stir the liquid epoxy resin dispersion and the loaded silicon diameter, and filter using a 110-mesh filter screen to obtain component A; S2, mix the aliphatic amine aqueous dispersion, propylene glycol methyl ether, and 10g of water for 20min at a stirring speed of 600r / min to obtain component B.

[0039] The use method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating is as follows: continuously stirring component A, adding component B in the stirring process, continuing to stir for 18 min after the addition is completed, and filtering through a 50-mesh filter screen.

[0040] Example 4

[0041] A low-VOC high-performance ship anticorrosive and antifouling integrated coating, raw materials of which include: 37 g of liquid epoxy resin dispersion, 2 g of loaded silicon dioxide, 4 g of graphene oxide, 8 g of mica powder, 18 g of titanium phosphate, 1.5 g of sodium hexametaphosphate, 12 g of aliphatic amine aqueous dispersion, and 2 g of propylene glycol methyl ether.

[0042] The loaded silicon dioxide is prepared by the following steps: 1.8 g of cetyltrimethylammonium chloride is added to 52 g of 40% mass fraction ethanol aqueous solution and stirred uniformly, 1.5 g of triethanolamine is added, the pH value of the system is adjusted to 9-10, 9 g of tetraethyl orthosilicate and 1.2 g of mercaptopropyl triethoxysilane are added thereto under nitrogen protection in a stirring state, reflux stirring is carried out at a temperature of 68℃ for 80 min, 4 g of amino-terminated polyamide amine and 1.2 g of zinc acetate are added and continue to stir for 3 h, centrifugation, washing, and vacuum drying.

[0043] The preparation method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating includes the following steps: S1, 25 g of water is continuously stirred, mica powder, titanium phosphate, graphene oxide, and sodium hexametaphosphate are sequentially added in the stirring process, and continue to stir for 11 min at a stirring speed of 1300 r / min, liquid epoxy resin dispersion and loaded silicon dioxide are added and stirred uniformly, filtered through a 100-mesh filter screen to obtain component A; S2, aliphatic amine aqueous dispersion, propylene glycol methyl ether, and 9 g of water are mixed for 17 min at a stirring speed of 550 r / min to obtain component B.

[0044] The use method of the low-VOC high-performance ship anticorrosive and antifouiling integrated coating is as follows: continuously stirring component A, adding component B in the stirring process, and continuing to stir for 12 min after the addition is completed, and filtering through a 70-mesh filter screen.

[0045] Example 5

[0046] A low-VOC high-performance ship anticorrosive and antifouling integrated coating has the following raw materials: 35 g of liquid epoxy resin dispersion, 3 g of loaded silicon dioxide, 3 g of graphene oxide, 10 g of wollastonite powder, 15 g of zinc benzoate, 2 g of sodium hexametaphosphate, 10 g of aliphatic amine aqueous dispersion, and 3 g of propylene glycol methyl ether.

[0047] The supported silicon dioxide is prepared by the following steps: 1.5 g of cetyltrimethylammonium chloride is added to 55 g of an ethanol aqueous solution with a mass fraction of 35% and stirred uniformly, 2 g of triethanolamine is added, the pH value of the system is adjusted to 9-10, 8 g of tetraethyl orthosilicate and 1.5 g of mercaptopropyl triethoxysilane are added thereto under nitrogen protection in a stirring state, reflux stirring is carried out at a temperature of 65℃ for 90 min, 3 g of an amino-terminated polyamide amine and 1.5 g of zinc acetate are continuously stirred for 2.5 h, centrifugation, washing and vacuum drying are carried out.

[0048] The preparation method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises the following steps: S1, continuously stirring 30 g of water, sequentially adding wollastonite powder, zinc benzoate, graphene oxide and sodium hexametaphosphate during the stirring process, continuously stirring for 12 min at a stirring speed of 1200 r / min, adding liquid epoxy resin dispersion and supported silicon dioxide and stirring uniformly, filtering by using a 100-mesh filter screen to obtain component A; S2, mixing an aliphatic amine aqueous dispersion, propylene glycol methyl ether and 8 g of water for 18 min at a stirring speed of 500 r / min to obtain component B.

[0049] The use method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises the following steps: continuously stirring component A, adding component B during the stirring process, continuously stirring for 15 min after the addition is completed, and filtering by using a 60-mesh filter screen.

[0050] Comparative Example 1 A low-VOC high-performance ship anticorrosive and antifouling integrated coating, raw materials of which comprise: 35 g of liquid epoxy resin dispersion, 3 g of supported silicon dioxide, 3 g of graphene oxide, 10 g of wollastonite powder, 15 g of zinc benzoate, 2 g of sodium hexametaphosphate, 10 g of aliphatic amine aqueous dispersion and 3 g of propylene glycol methyl ether.

[0051] The supported silicon dioxide is prepared by the following steps: 1.5 g of cetyl trimethylammonium chloride is added to 55 g of an ethanol aqueous solution with a 35% mass fraction and stirred uniformly, 2 g of triethanolamine is added, the pH value of a system is adjusted to 9-10, 8 g of tetraethyl orthosilcate and 1.5 g of mercaptopropyl triethoxysilane are added to the system under nitrogen protection in a stirring state, reflux stirring is carried out at a temperature of 65 ℃ for 90 min, 1.5 g of zinc acetate is continuously stirred for 2.5 h, centrifugation, washing and vacuum drying are carried.

[0052] The preparation method of the low-VOC high-performance ship anticorrosive and antifoul ing integrated coating comprises the following steps: S1, continuously stir 30g water, and then add wollastonite powder, zinc benzoate, graphene oxide, and sodium hexametaphosphate in sequence, continue to stir for 12min at a stirring speed of 1200r / min, add liquid epoxy resin dispersion and loaded silicon dioxide, stir uniformly, filter with a 100-mesh filter screen, and obtain component A; S2, mix aliphatic amine aqueous dispersion, propylene glycol methyl ether, and 8g water for 18min at a stirring speed of 500r / min, and obtain component B.

[0053] The use method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating is as follows: continuously stir component A, add component B in the stirring process, continue to stir for 15min after the addition is completed, and filter with a 60-mesh filter screen.

[0054] Comparative Example 2 A low-VOC high-performance ship anticorrosive and antifouling integrated coating, which comprises the following raw materials: liquid epoxy resin dispersion 35g, loaded silicon dioxide 3g, graphene oxide 3g, wollastonite powder 10g, zinc benzoate 15g, sodium hexametaphosphate 2g, aliphatic amine aqueous dispersion 10g, and propylene glycol methyl ether 3g.

[0055] The loaded silicon dioxide is prepared by the following steps: 1.5g of cetyltrimethylammonium chloride is added to 55g of 35% mass fraction ethanol aqueous solution and stirred uniformly, 2g of triethanolamine is added, the pH value of the system is adjusted to 9-10, 8g of tetraethyl orthosilicate is added under nitrogen protection in a stirring state, reflux stirring is carried out at a temperature of 65℃ for 90min, 3g of amino-terminated polyamide amine and 1.5g of zinc acetate are added, and continue to stir for 2.5h, then centrifugal, washing, and vacuum drying are carried out.

[0056] The preparation method of the low-VOC high-performance ship anticorrosive and antifouling integrated coating comprises the following steps: S1, continuously stir 30g water, and then add wollastonite powder, zinc benzoate, graphene oxide, and sodium hexametaphosphate in sequence, continue to stir for 12min at a stirring speed of 1200r / min, add liquid epoxy resin dispersion and loaded silicon dioxide, stir uniformly, filter with a 100-mesh filter screen to obtain component A; S2, mix aliphatic amine aqueous dispersion, propylene glycol methyl ester, and 8g water for 18min at a stirring speed of 500r / min to obtain component B.

[0057] The use method of the low-VOC high-performance ship anticorrosive and antifoul ing integrated coating is as follows: continuously stir component A, add component B in the stirring process, and continue to stir for 15min after the addition is completed, and filter with a 60- mesh filter screen.

[0058] The paint obtained in Example 5 and Comparative Examples 1-2 was sprayed as follows: a steel plate (washed and polished) with a trade name of Q195 was used as a substrate, and the substrate surface was sprayed 3 times using a high-pressure airless spraying method, a spraying gun pressure was 15 MPa, and a spraying gun moving speed was 1 m / s; a film thickness of each spraying was 45 ± 5 μm, and a total coating thickness was 135 ± 10 μm.

[0059] The impact resistance of each group of coating films was determined with reference to GB / T 1732-2020 “Paint Film Impact Resistance Test Method”, and the maximum height without cracks was used to represent the impact resistance. The adhesion of each group of coating films was determined with reference to GB / T 5210-2006 “Color Paint and Varnish Pull-off Method Adhesion Test”.

[0060] As shown in Figure 1 , the impact resistance and adhesion of the coating layer prepared from the paint obtained in Example 5 were the highest, and were significantly better than those of Comparative Examples.

[0061] The water resistance, acid resistance (10% hydrochloric acid), salt mist resistance, and humidity resistance of each group of coating films were tested with reference to GB / T 1733-1993 “Paint Film Water Resistance Test Method”, GB / T 10125-2012 “Artificial Atmosphere Corrosion Test Salt Spray Test”, and GB / T 1740-2007 “Paint Film Humidity Resistance Test Method”. The results are shown in Table 1.

[0062] Table 1 Coating layer results of the paint obtained in Example 5 and Comparative Examples 1-2

[0063] As can be seen from Table 1, the coating layer prepared from the paint obtained in Example 5 has excellent water resistance and long-term corrosion prevention ability.

[0064] With reference to GB / T 5370-2007 “Antifouling Paint Panel Shallow Sea Immersion Test Method”, each group of panels was marked before being immersed in the sea, and the original state was recorded. The immersion depth of the panels was 2 m. The immersed panels were fixed vertically and firmly on the frame, the surface of the panel was parallel to the main tidal flow of the seawater, and the spacing of the frame was greater than or equal to 200 mm. After the panels were immersed in the sea, the attached area of mussels, mollusks, and algae, etc. on the panels was observed regularly, and the observation room was removed by 20 mm along the edge of the panel to eliminate the edge effect. The observation time was shortened as much as possible, and the surface of the panel was photographed to evaluate the antifouling performance of the experimental panel, and the panel was immediately immersed in the sea after observation to avoid the death of the attached organisms, which would affect the observation results.

[0065] The coverage area of ​​fouling organisms is measured using a percentage plate with the same observation area as the sample. When evaluating test samples or control samples within the same frame, if the coverage area of ​​fouling organisms differs by 5%, the average value is taken. Otherwise, the average value of the two samples with larger coverage areas of fouling organisms is used to calculate the test result.

[0066] like Figure 2 As shown, the coating made with the coating obtained in Example 5 consistently had the lowest percentage of biofouling coverage, significantly lower than the comparative example, demonstrating excellent resistance to marine biofouling.

[0067] The present invention has been described in detail above. Those skilled in the art will recognize that the invention can be practiced in a wide range of ways with equivalent parameters, concentrations, and conditions without departing from its spirit and scope, and without requiring unnecessary experiments. While specific embodiments have been provided, it should be understood that further modifications can be made to the invention. In summary, according to the principles of the invention, this application is intended to include any changes, uses, or improvements to the invention, including changes made using conventional techniques known in the art that depart from the scope disclosed herein.

Claims

1. A low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships, characterized in that, The raw materials, by weight, include: 30-40 parts of waterborne epoxy emulsion, 1-5 parts of supported silica, 1-5 parts of graphene oxide, 5-15 parts of filler, 10-20 parts of anti-rust pigment, 1-3 parts of dispersant, 5-15 parts of aliphatic amine waterborne dispersion, and 1-5 parts of propylene glycol methyl ether.

2. The low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships according to claim 1, characterized in that, Waterborne epoxy emulsions are liquid epoxy resin dispersions.

3. The low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships according to claim 1, characterized in that, The anti-rust pigment is at least one of zinc phosphate, titanium phosphate, zinc benzoate, and aluminum tripolyphosphate; the filler is at least one of precipitated barium sulfate, wollastonite powder, kaolin, and mica powder.

4. The low-VOC, high-performance integrated anti-corrosion and anti-fouling coating for ships according to claim 1, characterized in that, The dispersant is a sodium hexametaphosphate type dispersant.

5. The low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships according to claim 1, characterized in that, The loaded silica was prepared by the following steps: hexadecyltrimethylammonium chloride was added to an aqueous ethanol solution and stirred until homogeneous. Triethanolamine was added, and the pH of the system was adjusted to 9-10. Under nitrogen protection, tetraethyl orthosilicate and mercaptopropyltriethoxysilane were added while stirring. The mixture was refluxed at 60-70°C for 1-2 hours. Amino-terminated polyamide amine and zinc acetate were added, and stirring was continued for 1-4 hours. The mixture was then centrifuged, washed, and vacuum dried.

6. The low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships according to claim 5, characterized in that, The mass ratio of hexadecyltrimethylammonium chloride, triethanolamine, tetraethyl orthosilicate, mercaptopropyltriethoxysilane, amino-terminated polyamide amine, and zinc acetate is 1-2:1-3:5-10:1-2:1-5:1-2.

7. The low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships according to claim 5, characterized in that, The mass fraction of the ethanol aqueous solution is 20-50%.

8. A method for preparing a low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Continuously stir the water, and add filler, anti-rust pigment, graphene oxide and dispersant in sequence during the stirring process. Continue stirring for 10-15 minutes, add water-based epoxy emulsion and loaded silica and stir evenly. Filter to obtain component A. S2. Mix the aliphatic amine aqueous dispersion, propylene glycol methyl ether, and water for 15-20 minutes to obtain component B.

9. The preparation method of the low-VOC high-performance integrated anti-corrosion and anti-fouling coating for ships according to claim 8, characterized in that, In S1, a 90-110 mesh filter is used for filtration.

10. A method of using a low-VOC, high-performance integrated anti-corrosion and antifouling coating for ships as described in any one of claims 1-7, characterized in that, Continue stirring component A, add component B during the stirring process, and continue stirring for 10-20 minutes after the addition is complete, then filter.